Melchizedek Passages in the Bible. A Case Study for Inner-Biblical and Inter-Biblical Interpretation - Alan KamYau, Chan (De Gruyter, 2016)
Melchizedek is a mysterious figure to many people. Adopting discourse analysis and text-linguistic approaches, Chan attempts to tackle the Melchizedek texts in Genesis 14, Psalm 110, and Hebrews 5-7. This seminal study illustrates how the mysterious figure is understood and interpreted by later biblical writers, "... Using the "blessing" motif as a framework, Chan also argues that Numbers 22-24, 2 Samuel 7 and the Psalter: Books I-V (especially Psalms 1-2) provide a reading paradigm of interpreting Psalm 110. In addition, the structure of Hebrews provides a clue to how the author interprets the Old Testament texts.